Let their Knowledge Flow: The Effect of Returning Refugees on Export Performance in the Former Yugoslavia - Dany Bahar; Andreas Hauptmann; Cem Özgüzel; Hillel Rapoport (Center for Economic Studies and ifo Institute (CESifo), 2018)
During the early 1990s Germany received over half a million Yugoslavian refugees fleeing war. By 2000, many of these refugees, who were under temporary protection, had been repatriated. We exploit this historical episode to provide causal evidence on the role that migrants play explaining export performance in global markets after returning to their home country. We find that the elasticity of exports to return migration is between 0.1 to 0.24 in industries where migrants were employed during their stay in Germany. In order to deal with endogeneity we use historic exogenous rules of allocation of asylum seekers across different German states to construct an instrumental variable for the treatment. The results are mostly driven by knowledge-intensive industries, and by workers in occupations intensive in analytical and managerial skills.
Keywords: F14; F22; F62; O33; D83; 330; migration; refugees; knowledge diffusion; management; exports; productivity